Reaksi Perekonomian Rusia Ditengah Pandemi Covid-19 - Refly Setiawan; Abdurrahman Abdurrahman; Gine Putri Pertiwi; Sherly Saputri (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:Currently, the world is facing various problems, one of which is the Covid-19 outbreak which is attacking humans all over the world. All countries are trying to fight against the spread of the virus, one of which is Russia. Russia is a country located in the eastern European region and has an economic system that can be said to be good. However, at this time economic conditions around the world are in a critical condition and are worsening due to the increasingly rapid spread of Covid-19 and causing the death of both humans and the economy of a country which is slowly paralyzing. This paper aims to find out how the Russian state's economic reaction in the midst of the Covid-19 pandemic which is currently still happening and cannot be stopped and how the government's actions are in response to the economy which is getting worse amid the Covid-19 pandemic.Keywords: Economy, Russian State, Government Response, Covid-19 PandemicAbstrak: Saat ini kondisi dunia sedang dihadapkan dengan berbagai masalah salah satunya adalah wabah Covid-19 yang sedang menyerang manusia diseluruh belahan dunia. Seluruh negara saling berupaya untuk melawan penyebaran virus tersebut, salah satunya yaitu negara Rusia. Rusia merupakan negara yang terletak di wilayah Eropa timur dan memiliki sistem perekonomian yang dapat dikatakan baik. Akan tetapi, pada saat ini kondisi perekonomian di seluruh dunia sedang dalam kondisi kritis dan terpuruk dikarenakan penyebaran Covid-19 yang semakin cepat dan menyebabkan kematian baik manusia maupun perekenomian suatu negara yang perlahan-lahan lumpuh. Tulisan ini bertujuan untuk mengetahui bagaimana reaksi perekonomian negara Rusia ditengah pandemi Covid-19 yang saat ini masih terjadi dan belum dapat dihentikan dan bagaimana tindakan pemerintah dalam menyikapi perekonomian yang semakin terpuruk ditengah masa pandemi Covid-19.Kata Kunci: Perekonomian, Negara Rusia, Respon Pemerintah, Pandemi Covid-19